Using technology project based learning to enhance learners autonomy / Aznizah Abdul Rahman - Abdul Rahman, Aznizah (2010)
Project Based Learning (PBL) is not a new thing in Malaysia. However, students were still taught using the traditional approach aided with textbooks and predesigned activity books. This led to the belief that Malaysian students rarely had the chance to demonstrate their autonomy as their learning was confined to limited sources. This study therefore aimed to explore the relationship between the implementation of Technology Project Based Learning (TPBL) and learners autonomy, focusing on learners control over their learning. The challenges faced by the students in completing their project were also identified in the study. A qualitative case study method was selected to carry out the study. The participants involved in this study were 36 form four students from an urban secondary school. The students were encouraged to work independently using ICT to I complete their project. The data ofthe study were acquired through a detailed analysis of the respondents' journals, classroom observation as well as interviews with the participants. The findings ofthe study indicated that TPBL had a significant impact on the students. It promoted the students to have better control over their learning making them more autonomous. Their experience in TPBL not only made them more skillful in using the various programmes, but they were also aware ofthe vast benefits ofICT in their learning. The students participated actively throughout the project, improving their communication skills and enhancing their higher order thinking skills. A framework was also developed from the findings of the study on the elements affecting learners' control in TPBL. The framework showed that the elements affecting learner's control in TPBL for this particular group of students are the facilities provided and the authenticity of the task. In applying TPBL with the secondary school students, teachers therefore need to take these two factors into consideration so that the project done could enhance their knowledge as well as help them build positive characters.